1975
DOI: 10.1111/j.1749-6632.1975.tb51080.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations in Vinyl Chloride Poisoning

Abstract: As civilization developed, man passed through the Stone Age, the Iron Age, and the Bronze Age. Now we are living in the Plastics Age.As supplies of iron, copper, lead, and other metals decrease, they are replaced mostly by plastics. The conquest of space and Mount Everest, the rapid development of industry, and the higher standard of hygiene and clothing would not have been possible without the development of the plastics industry.Plastics are obtained from salt, petroleum, wood, methane, gas, quartz, etc. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…Recently, Hirano et al suggested that glutathione conjugates of arsenic are toxic in rat heart micro-vessel endothelial cells (Hirano et al 2004). In many studies, endothelial damage has probably occurred because several studies have documented vascular injury and microvascular lesions in CVM disease (Suciu et al 1975;Fallappa et al 1982;Maricq et al 1976;Freudiger et al 1988). However, to date, no experimental endothelial toxicity of any VCM metabolites, whether conjugated or not, has been documented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Hirano et al suggested that glutathione conjugates of arsenic are toxic in rat heart micro-vessel endothelial cells (Hirano et al 2004). In many studies, endothelial damage has probably occurred because several studies have documented vascular injury and microvascular lesions in CVM disease (Suciu et al 1975;Fallappa et al 1982;Maricq et al 1976;Freudiger et al 1988). However, to date, no experimental endothelial toxicity of any VCM metabolites, whether conjugated or not, has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…The first cases of RP were recorded in workers called autoclave cleaners, who were lowered into reactor vessels to clean polymer residues stuck to the walls manually; these were usually the highest VCMexposed jobs in PVC-polymerisation plants (Wilson 1967;Harris and Adams 1967;Veltman et al 1975;Suciu et al 1975;Maricq et al 1976;Markowitz et al 1977). However, other cases have since been described in VCM-exposed workers who had never been employed for this type of job or who had worked in less exposed workplaces (Black et al 1986;Walker 1976;Freudiger et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this difficulty, emulsion process plants tend to emit more vinyl chloride monomer to the ambient air per pound of resin produced. In Europe particularly there have been reports of worker dermatitis from surfactants and possible pneumoconiosis from resin dust inhalation in the emulsion process plants (2)(3)(4).…”
Section: October 1981 125mentioning
confidence: 99%